"I try and smile, I try and be cheery, I try not to be pushy. I try to say 'I'm here for help' but I leave feeling... worried": a qualitative study of perceptions of interactions with health professionals by community-based older adults with chronic pain. - Amanda Clarke (Public Library of Science (PLoS), 2014)
Background Over 50% of community-dwelling older adults experience chronic pain, which threatens their quality of life. Of importance to their pain management is older people's interaction with health professionals that, if unsatisfactory, may impair the outcome. Aims To add to the limited research specific to older people living with chronic pain in the community, we explored how they perceive their experiences of interacting with health professionals, seeking factors that might optimise these interactions. Methods Purposive sampling was used to recruit men and women >65 years with self-reported musculoskeletal chronic pain. Qualitative individual interviews and one group interview were undertaken with 23 participants. Data were transcribed verbatim and underwent Framework Analysis. Results Three themes were identified. Seeking help illustrates issues around why older people in the community may or may not seek help for chronic pain, and highlights the potential involvement of social comparison. Importance of diagnosis illustrates the desire for professional validation of their condition and an aversion to vague explanations based on the person's age. Being listened to and being heard illustrates the importance of empathic communication and understanding expectations, with due respect for the person's age. Conclusions In common with people of all ages, an effective partnership between an older person in pain and health professionals is essential if pain is to be reported, appropriately assessed and managed, because of the subjective nature of pain and its treatment responses. For older people with pain, perception about their age, by both parties in the partnership, is an additional factor that can unnecessarily interfere with the effectiveness of this partnership. Health professionals should engage with older adults to clarify their expectations about pain and its management, which may be influenced by perceptions about age; and to encourage expression of their concerns, which may also be affected by perceptions about age.